2001
DOI: 10.1186/bcr295
|View full text |Cite
|
Sign up to set email alerts
|

Low frequency of E-cadherinalterations in familial breast cancer

Abstract: In order to explore the possible role of E-cadherin in familial cancer, 19 familial breast cancer patients, whose tumours demonstrated loss of heterozygosity (LOH) at the E-cadherin locus, were screened for germline mutations. No pathogenic germline alterations were detected in these individuals. However, a somatic mutation was found (49-2A→C) in one of the tumours. This tumour showed a pattern of both ductal and lobular histology. Another 10 families with cases of breast, gastric and colon cancer were also sc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
26
1
2

Year Published

2001
2001
2010
2010

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 42 publications
(30 citation statements)
references
References 33 publications
1
26
1
2
Order By: Relevance
“…Among the various IDC types, negative expression was characteristically observed in both the cases of IDC with comedo necrosis. Salahshor et al 32 reported a germline E-CD alteration (Aa592Thr) in cases of IDCs with comedo necrosis, which was considered to be responsible for phenotypic divergence of this variant from other IDC types, thereby forming an underlying reason for its negative expression in the present study. This further substantiates aggressive behavior of this tumor type.…”
Section: Discussionmentioning
confidence: 48%
“…Among the various IDC types, negative expression was characteristically observed in both the cases of IDC with comedo necrosis. Salahshor et al 32 reported a germline E-CD alteration (Aa592Thr) in cases of IDCs with comedo necrosis, which was considered to be responsible for phenotypic divergence of this variant from other IDC types, thereby forming an underlying reason for its negative expression in the present study. This further substantiates aggressive behavior of this tumor type.…”
Section: Discussionmentioning
confidence: 48%
“…[18][19][20][21] Abnormal Ecadherin in breast carcinomas has been associated mainly with E-cadherin promoter methylation and very few mutations in the gene have been reported. 22,23 Previous studies showed that decreased immunoreactivity of E-cadherin statistically correlated with the presence of lymph node metastases in esophageal squamous cell carcinoma, and loss of intercellular adhesion activates a transition from low-to high-grade squamous cell carcinoma, thus indicating an important role for E-cadherin as a prognostic marker in the progression of tumors. 24,25 Increased expression of the 80 kDa fragment of E-cadherin in metastatic prostate cancer in association with increased levels of several metalloproteinases, which are believed to be responsible for cleavage of short E-cadherin fragment from the full-length Ecadherin, are suggested to induce tumor progression in this tumor.…”
Section: Discussionmentioning
confidence: 99%
“…In one of the families the occurrence of lung and rectal cancer was reported , but the detailed history of the other family was not described (Moran et al, 2005). A somatic 49-2A>C mutation has been shown in a breast tumour of both ductal and lobular histology (Salahshor et al, 2001).…”
Section: Familymentioning
confidence: 99%